2019
DOI: 10.1021/acs.joc.9b01492
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Effects of Picoloyl Groups in Sialylations Based on Their Substitution Pattern

Abstract: A novel 8-O-picoloylated sialyl donor has been developed, and the performance of various picoloylated sialyl donors in glycosylations with primary glycosyl acceptors has been evaluated. 8-O-Picoloyl and 4,9-di-O-picoloyl sialyl donors produced moderate to excellent yields of disaccharides with complete α-stereoselectivities. Synergistic effects between picoloyl and the accompanying O-protecting groups (benzoyl vs acetyl) were evaluated, as well as the effects of triflic acid concentration on the 8-O-picoloyl d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…As we know that the concentrations of reactants can affect the outcome of glycosylation [ 31 , 33 34 37 , 39 , 43 44 46 , 56 57 ], one must choose a concentration at which to perform the test glycosylation. This can be done either by analogy with similar reactions or by utilizing some rationalization, the second approach is more attractive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we know that the concentrations of reactants can affect the outcome of glycosylation [ 31 , 33 34 37 , 39 , 43 44 46 , 56 57 ], one must choose a concentration at which to perform the test glycosylation. This can be done either by analogy with similar reactions or by utilizing some rationalization, the second approach is more attractive.…”
Section: Resultsmentioning
confidence: 99%
“…However, the reliable installation of sialic acid residues in oligosaccharides is a rather difficult issue and poor predictability remains characteristic of the sialylation reaction [ 16 21 ]. As in other glycosylation reactions [ 22 29 ], the result of sialylation is affected by a variety of variables [ 30 39 ] including the nature of protective groups on either partner [ 26 , 38 , 40 45 ] and concentration of reagents [ 31 , 33 34 37 , 39 , 43 44 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…De Meo et al. reported that C4,C9‐di‐ O ‐picoloyl donor 113 and C8‐ O ‐picoloyl sialyl donor 114 exhibited complete α‐stereoselectivity [63b] . In many cases, picoloyl‐protected donors required an excess of TfOH (1.5–2.0 equiv.)…”
Section: Synthesis Of α‐Sialosidesmentioning
confidence: 99%
“…They (2019) further extended their study to described the effects of picoloyl groups based on their position and number and also reported a novel synthesis of several mono-as well as di-O-picoloyl sialyl donors (127 to 132) to obtained disaccharides in moderate to excellent yields with better αstereoselectivities. [51] In support of their proposed strategy, they first used mono-picoloylated donors 127-130 activated by triflic acid and coupled with standard primary benzyl-protected galactosyl acceptors 2 to furnish the corresponding disaccharide (133 a-d) with α-selectivity exclusively. However, the complete α-selectivity obtained in the case of donor 129 while poor selectivity was obtained in the case of donor 130, and the case of donor 127 &128 moderate selectivity was observed.…”
Section: Sialyl Donorsmentioning
confidence: 99%